Developments in the synthesis of α,α-dibromoacetophenones and related compounds - Arora, Loveena; Prakash, Richa; Pundeer, Rashmi (Synthetic communications, 2019)
Increasing demand of α,α-dibromoketones, as highly reactive and easy-to-handle precursors to carry out selective organic transformations, to synthesize heterocyclic compounds of therapeutic interest and lack of any compilation on this subject prompted us to assemble the methods available for their synthesis.